2018
DOI: 10.1007/s13197-018-3395-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of sulforaphane stability in blanched and un-blanched broccoli (Brassica oleracea var. italica) florets during storage at low temperatures

Abstract: Sulforaphane is a health-promoting compound found in broccoli. Given its high thermo-lability, its preservation through high-temperature processes seems inconvenient. Accordingly, storage at low temperature is an alternative. There are no studies about the evolution of sulforaphane content during storage at low temperatures. The change of sulforaphane content in blanched and unblanched broccoli florets during storage at 10,-1,-21 and-45°C for 83 days was studied. In blanched broccoli, sulforaphane content foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Sulforaphane (4-methylsulfinylbutyl isothiocyanate, SFN) is a phytochemical produced from a biologically inactive precursor, glucoraphanin, during the biting and chewing of certain plant sources [5][6][7][8][9]; this precursor is found in cruciferous vegetables and many nutraceuticals [10]. SFN is usually well tolerated and is known to exert potent antioxidant effects by modifying cytoplasmic KEAP1 conformation, releasing NRF2 for nuclear translocation and the transcriptional activation of genes with antioxidant response elements (ARE) in their promoters [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (4-methylsulfinylbutyl isothiocyanate, SFN) is a phytochemical produced from a biologically inactive precursor, glucoraphanin, during the biting and chewing of certain plant sources [5][6][7][8][9]; this precursor is found in cruciferous vegetables and many nutraceuticals [10]. SFN is usually well tolerated and is known to exert potent antioxidant effects by modifying cytoplasmic KEAP1 conformation, releasing NRF2 for nuclear translocation and the transcriptional activation of genes with antioxidant response elements (ARE) in their promoters [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (4-methylsulfinylbutyl isothiocyanate, SFN) is a phytochemical produced from a biologically inactive precursor, glucoraphanin, during biting and chewing of certain plant sources [5][6][7][8][9]; this precursor is found in cruciferous vegetables and many nutraceuticals [10]. SFN is usually well tolerated and is known to exert potent antioxidant effects by modifying cytoplasmic KEAP1 conformation, releasing NRF2 for nuclear translocation and transcriptional activation of genes with antioxidant response elements (ARE) in their promoters [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Glucoraphanin converts into sulforaphane on a one-to-one stoichiometric mole basis. We found that a glucoraphanin concentration range between 0.88-1.10 μmol/g is common in fresh-weight broccoli microgreens [10]. Based on literature values, we assumed an average microgreens sample comprises a 0.85 μmol/g glucoraphanin concentration [11].…”
Section: Project 1: the Impact Of Variable Glucosinolate Degradation ...mentioning
confidence: 99%
“…kd,ref represents the degradation rate constant in minutes at Tref, a reference temperature chosen to be 100°C or 373 K. The reference data was used to identify a sample degradation rate constant at 25°C or 98 K for kd,ref = 2.07×10 -2 per minute using an Arrhenius-type model. The activation energy for glucoraphanin degradation, Ea, is 159 J/mol [10].…”
Section: Project 1: the Impact Of Variable Glucosinolate Degradation ...mentioning
confidence: 99%